A Profile of Patients with Molar Pregnancy - Bhatta, Rabindra Dev; Rijal, P; Pradhan, T; Chhetri, S; Rai, R; Uprety, DK (Nepal Journal of Obstetrics and Gynaecology, 2017)
Aims: This study was done to determine the incidence, modes of presentation and prognosis of molar pregnancy at B. P. Koirala Institute of Health Sciences. Methods: This was a prospective study done among patients with molar pregnancy admitted at BPKIHS from January 2010 to January 2011. The study was conducted after ethical clearance from Institutional Ethical Review Board of BPKIHS. Written informed consent was taken for enrollment in the study. Baseline information like age, address, race and patient’s presenting complaints, period of gestation and serial serum beta human chorionic gonadotropin (βhCG) were collected and analyzed after entering in excel sheet. Results: Total 48 cases of molar pregnancy were diagnosed during the study period. The incidence of molar pregnancy was found to be 5.58 per 1000 deliveries. The most common mode of presentation was per vaginal bleeding i.e. in 64.58% of cases. Majority of the patients were in the age group of 20-34 years (62.5%). Mean time for normalization of βhCG after suction evacuation was 10.19 weeks. Conclusions: Molar pregnancy is a pregnancy related problem which most commonly presents with per vaginal bleeding during first and second trimester. Most of the patients are treated with suction and evacuation but some develop persistent gestational trophoblastic disease.